TRUDNA ROSYJSKA DROGA DO NIEZALEŻNYCH MEDIÓW (AGENCJE INFORMACYJNE, KORPORACYJNE ŚRODKI MASOWEGO PRZEKAZU, PRASA) - Gorgosz, Daniel (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Media market experts unanimously stress an important contribution of news agencies to the devel¬opment of Russian media. The leading agencies are, apart from TASS and APN (the Novosti Press Agency), which used to be monopolists in the past, in the first place RIA-Novosti, Lenta.ru, Agent¬stvo Evropejskikh Novostey and Gorod 24. An important factor is the corporate magazine, being a tool for creating a positive corporation image, and an additional source of income. Though the Russian media are all the time vigorously expanding, one cannot fail to notice their biased coverage of current affairs, for example comments on events related to the social protests in Ukraine, as well as lampooning members of the Pussy Riot group in the leading newspapers. The situation is made worse by the propaganda character of the Russia Today TV channel.